A new distance based route maintenance strategy for dynamic source routing protocol - Sjaugi, Muhammad Farhan; Othman, Mohamed; A. Rasid, Mohd Fadlee (Science Publications, 2008)
Although DSR can respond a route quickly, it yields a long delay when a route is rebuilt. This is because when source node receives RERR packet, it will try to find alternative routes from the route cache. If alternative routes are not available, the source node, then, will enter route discovery phase to find new routes. We introduced a new route maintenance strategy by utilizing location information, called the DISTANCE (DIstance baSed rouTe maintenANCE) algorithm. The DISTANCE algorithm works by adding another node (called bridge node) into the source list to prevent the link from failure. From the simulation result, the DISTANCE algorithm improved the performance of DSR in terms of packet sending ratio, delay and routing overhead.